EXPERIMENTAL STUDY ON THE FLEXURAL BEHAVIOUR OF RETROFITTED RC-BEAMS USING NEAR SURFACE MOUNTED TECHNIQUE AND BFRP SHEETS - DR. R.R. SINGH; MISS. AASTHA (International Journal of Innovations in Engineering Research and Technology, 2021)
Structures are in a phase of faster deterioration due to adverse environmental conditions. Most of the reinforced concrete structures reached their life time and time has come to repair/strengthen them. Variousretrofitting techniques have been started in the field of construction and a brief of some of the techniques is mentioned in the study. The awareness among the people regarding retrofitting techniques is quite low. This study primarily deals with the use of Basalt Fiber Reinforced Polymer bars and sheets for strengthening the RC beams. In this work the BFRP bars and sheets are used to enhance the flexural capacity of the RC beams under four-point loading conditions and retrofitted at various pre-loading conditions. The load deflection characteristics are studied for various pre-loading conditions using BFRP bars, sheets and the combinations. The BFRP bars and sheets are introduced into the pre-cracked beam by the use of epoxy adhesive. The study considered the comparison of retrofitted beam of 50% & 70% preloading conditions with the control beam. The enhancement of ultimate load carrying capacity was above 25% in all the cases also the use of bi-directional BFRP sheets increased the capacity by more than 40% and the combinations increased the capacity by more than 50%. Slipping/de-bonding is not observed in the bars but the sheets showed de-bonding with the concrete under ultimate loading conditions.